ANALISIS PENGARUH PERSEPSI ATAS ORIENTASI PELANGGAN DAN REPUTASI PERUSAHAAN TERHADAP ORIENTASI PELAYANAN STRATEGIK DAN DAMPAKNYA PADA KEPUASAN PELANGGAN - Robby Jatmiko (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2015)
This research analyzes the effect of perception on customer orientationand perception on company reputation on perception of strategic serviceorientation and its impact on customer satisfaction. The research problem isbased on 2 (two) issues: first is research gap based on previous researchbackground for example, referring to the borders and direction of researchwill come on and inconsistent with previous findings such as in Homburg etal., ( 2002); Chenet et al., (2000); Pelham, (1997); Doney and Cannon(1997). And the second comes from the research problems, which is found inthe data that gives an overview of the condition of PT. MandalatamaArmada Motor deals with the targets and sales realization of